Pivotal antitumor role of the immune checkpoint molecule B7-H1 in pancreatic cancer - Bazhin, Alexandr V.; Ahn, Katharina von; Fritz, Jasmin; Bunge, Henriette; Maier, Caroline; Isayev, Orkhan; Neff, Florian Matthias; Siveke, Jens T.; Karakhanova, Svetlana (OncoImmunology, 2022)
Immune checkpoint molecule B7-H1 plays a decisive immune regulatory role in different pathologies including cancer, and manipulation of B7-H1 expression became an attractive approach in cancer immunotherapy. Pancreatic cancer (PDAC) is characterized by pronounced immunosuppressive environment and B7-H1 expression correlates with PDAC prognosis. However, the first attempts to diminish B7-H1 expression in patients were not so successful. This points the complicity of PDAC immunosuppressive network and requires further examinations. We investigated the effect of B7-H1 deficiency in PDAC. Our results clearly show that partial or complete B7-H1 inhibition in vivo let to reduced tumor volume and improved survival of PDAC-bearing mice. This oncological benefit is due to the abrogation of immunosuppression provided by MDSC, macrophages, DC and Treg, which resulted in simultaneous restoration of anti-tumor immune response, namely improved accumulation and functionality of effector-memory CD4 and CD8 T cells. Our results underline the potential of B7-H1 molecule to control immunosuppressive network in PDAC and provide new issues for further clinical investigations.